2015
DOI: 10.5194/acp-15-1843-2015
|View full text |Cite
|
Sign up to set email alerts
|

SO<sub>2</sub> photolysis as a source for sulfur mass-independent isotope signatures in stratospehric aerosols

Abstract: Abstract. Signatures of sulfur isotope mass-independent fractionation (S-MIF) have been observed in stratospheric sulfate aerosols deposited in polar ice. The S-MIF signatures are thought to be associated with stratospheric photochemistry following stratospheric volcanic eruptions, but the exact mechanism responsible for the production and preservation of these signatures is debated. In order to identify the origin and the mechanism of preservation for these signatures, a series of laboratory photochemical exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
75
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 70 publications
9
75
1
2
Order By: Relevance
“…X 1 A 1 ): SO 2 will be excited to at riplet state.T he first absorption band is difficult to investigate because there was no photocell window or laboratory light source available.Aseries of synchrotron experiments applied to varying molecules (CO,N 2 ,a nd H 2 S) [60-62, 64, 65, 144] open new areas for studying photochemically-induce isotope effects in the VUV range and investigation of SO 2 is currently underway. As shown in existing experiments,f or not only SO 2 [142,148] but also CO [61] and N 2 , [65] intersystem crossing is governed by many parameters such as column density and temperature.Their effects are difficult to predict because the exited state potential energy surfaces of varying isotopomers and corresponding vibrational/rotational energy distribution are impossible to accurately and precisely calculate at arequisite level. Therefore,e xisting studies were focused on the second and third absorption bands (i.e., photo-dissociation and photo-excitation bands,r espectively).…”
Section: Angewandte Chemiementioning
confidence: 84%
See 2 more Smart Citations
“…X 1 A 1 ): SO 2 will be excited to at riplet state.T he first absorption band is difficult to investigate because there was no photocell window or laboratory light source available.Aseries of synchrotron experiments applied to varying molecules (CO,N 2 ,a nd H 2 S) [60-62, 64, 65, 144] open new areas for studying photochemically-induce isotope effects in the VUV range and investigation of SO 2 is currently underway. As shown in existing experiments,f or not only SO 2 [142,148] but also CO [61] and N 2 , [65] intersystem crossing is governed by many parameters such as column density and temperature.Their effects are difficult to predict because the exited state potential energy surfaces of varying isotopomers and corresponding vibrational/rotational energy distribution are impossible to accurately and precisely calculate at arequisite level. Therefore,e xisting studies were focused on the second and third absorption bands (i.e., photo-dissociation and photo-excitation bands,r espectively).…”
Section: Angewandte Chemiementioning
confidence: 84%
“…[136] Tw om ajor discoveries in 2000 (the sulfur isotope mass independent composition in Martian meteorites [76] and Archean rocks [96] )r equired an additional mechanistic explanation because S 2 F 10 is not relevant and concentrations of CS 2 in the Martian and terrestrial atmospheres are too low to explain the observed effect. Thef irst series of SO 2 and H 2 S photochemistry experiments was conducted by Farquhar et al, [76,97] and confirmed that as ulfur isotope mass independent effect can be found in these photolytic reactions and qualitatively resemble observations in nature.A ll multiple sulfur isotope measurements in extraterrestrial and terrestrial samples (e.g., meteorites,rocks,ice cores,aerosols) in the first decade of the 21 st century were interpreted based on similar photochemistry.B ecause existing theoretical knowledge of sulfur isotope effect was not totally satisfied to explain observations,e xperimental investigations accelerated and broadened in the second decade of the 21 st century:T he cross sections of anumber of isotopomers ( 32 SO 2 , 33 SO 2 , 34 SO 2 , 36 SO 2 ,O C 32 S, OC 33 S, OC 34 S, O 13 CS) [137][138][139][140] were firstly determined in as eries of experiments (joint efforts by many scientists in Japan and Denmark:D anielache,H attori, Johnson, Schmidt, Ueno,a nd Yoshida) for advancing theoretical studies;U eno and colleagues expanded their experiments to SO 2 photolysis; [141] Farquhar and colleagues also revisited their early SO 2 photolysis experiment results by carrying out additional experiments; [142,143] H 2 Sp hotolysis experiments were extended to the VUV range by Chakraborty et al; [144] another series of photochemistry experiments (with am ajor focus on SO 2 [145][146][147][148] and expanded to COS [149] and phenacylphenylsulfone [150] )w as carried out by Ono and colleagues as well. Ar eview of detailed experimental results and theoretical interpretation was recently provided by Ono.…”
Section: Experimental and Theoretical Investigation Of Sulfur Isotopimentioning
confidence: 99%
See 1 more Smart Citation
“…The photolysis rate of SO 2 is much faster than the photoexcitation of SO 2 , which could also produce large MIF (Endo et al, 2016;Whitehill et al, 2015;Whitehill & Ono, 2012;Whitehill et al, 2013). The photolysis rate of SO 2 is much faster than the photoexcitation of SO 2 , which could also produce large MIF (Endo et al, 2016;Whitehill et al, 2015;Whitehill & Ono, 2012;Whitehill et al, 2013).…”
Section: Photochemical Experimentsmentioning
confidence: 99%
“…However, the actual chemical process, or processes, responsible for generation of significant enrichments of sulfur-bearing species in heavy isotopes of sulfur, and leading to mass-independent fractionation, still remains unidentified. Some mass-independent fractionation was observed experimentally in SO 2 photolysis (10-12) and in nonadiabatic dynamics of SO 2 photodissociation (13,14). Another important chemical pathway, specific to a low-oxygen atmosphere (7,8,(15)(16)(17), is a chain of recombination reactions that start from recombination of photolytically produced sulfur atoms (S + S → S 2 ), go through formation of larger sulfur allotropes (S + S 2 → S 3 , S 2 + S 2 → S 4 , and S + S 3 → S 4 ), and end up at the elemental sulfur (S 4 + S 4 → S 8 ) that can be deposited, preserved, and could contribute to S-MIF in the Archean atmosphere.…”
mentioning
confidence: 97%